MACROECONOMIC AND INTEGRATIVE ASPECTS OF THE FORMATION AND DEVELOPMENT OF TRANSPORT AND LOGISTICS SYSTEMS - Yarashova Vasila Kamalovna (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The article is devoted to topical problems of the development of transport and logistics systems associated with macroeconomic and integrative factors. To ensure the optimal functioning of the national economy, it is necessary to take into account the trends and dynamics of possible changes in macroeconomic proportions, which represent a gradual change in quantitative relationships between different sectors of the national economy. The author describes that the management of material flows at the regional, national or international level is one of the main directions of the macroeconomic policy of any state. Thus, it becomes obvious that transport is not just one of the elements of logistics, but the main means by which logistics, regardless of its scale, is pragmatically expressed in the existing reality. The article summarizes the scientific and practical experience of the functioning of logistics systems in foreign countries. The article presents the main achievements in the development of the transport and logistics system of Uzbekistan, large-scale structural and institutional transformations in transport, the indicators of the provision of the country's regions with public roads and railways are calculated, the dynamics of the main indicators of the development of the transport sector in the system of macroeconomic coordinates are given. The dynamic growth of the economy leads to a significant increase in the volume of goods movement and, accordingly, cargo flows, both domestic and international, including transit. But in conditions of insufficient development of the transport and logistics infrastructure, the productivity and efficiency of the country's transport complex, as a rule, decreases. The author has analyzed the shortcomings and problem areas that exist in the industry at the present time. There is a low level of multimodal transportation, logistics, customs, forwarding and other services. There is a lack of coordination between customs services of countries and no integrated information systems for cargo tracking. Some customs posts at international checkpoints are poorly equipped with the necessary devices and equipment.